Manufacturing method for lithium iron phosphate cathode material
Patent Information
- Application Number
- JP2023078927
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-09-27
- Filing Date
- 2023-05-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-05-11
AI Technical Summary
【0008】 上記の目的を達成するために、本発明の実施形態は、リン酸、鉄粉および炭素源を提供し、リン酸が鉄粉と反応して第1生成物を生成し、第1生成物が非晶質のリン酸鉄であり、化学式がa-FePO4·xH2Oであり、x>0である、ステップ(a)と、リチウム塩混合物を提供し、リチウム塩混合物は、水酸化リチウムと炭酸リチウムとを含有するステップ(b)と、第1生成物、炭素源およびリチウム塩混合物を粉砕混合するステップ(c)と、第1生成物とリチウム塩混合物とを焼結して前駆体を形成し、前駆体の化学式がFe3(PO4)2·8H2O+Li3PO4であるステップ(d)と、前駆体と炭素源とを焼結してリン酸鉄リチウム正極材料を形成するステップ(e)とを含む、ことを特徴とするリン酸鉄リチウム正極材料の製造方法を提供する。 好ましくは、リチウム塩混合物のリチウム含有量に対する水酸化リチウムのリチウム含有量を第1モル分率とし、第1モル分率が0.5~0.7である。 好ましくは、リチウム塩混合物のリチウム含有量に対する炭酸リチウムのリチウム含有量を第2モル分率とし、第2モル分率が0.3~0.5である。 好ましくは、ステップ(c)において、第1生成物、炭素源およびリチウム塩混合物のpH値が9以下である。 好ましくは、ステップ(c)において、第1生成物、炭素源およびリチウム塩混合物のpH値が7.5~9である。 好ましくは、リン酸鉄リチウム正極材料は、炭素被覆のあるナノ金属酸化物共結晶化リン酸鉄リチウム化合物である((LFP Nano Cocrystalline Olivine, LFP-NCO)。 好ましくは、ステップ(a)は、さらに、第1温度環境において、第1所定量の前記リン酸を脱イオン水に溶解して第1リン酸溶液を形成するステップ(a1)と、第2温度環境において、第1リン酸溶液と鉄粉とを反応させ、且つ第2温度に達した後、第3温度に降温して第1の時間維持するステップ(a2)と、第4温度に降温し、第2所定量のリン酸を含有する第2リン酸溶液を添加し、第1リン酸溶液、第2リン酸溶液および鉄粉を第2の時間反応させ、第1生成物を生成するステップ(a3)とを含む。 好ましくは、第1所定量と第2所定量との重量比が3:1である。 好ましくは、第1温度が35℃~45℃であり、第2温度が60℃以下であり、第3温度が50℃以下であり、第4温度が30℃以下である。 好ましくは、第1の時間が少なくとも3時間であり、第2の時間が少なくとも18時間である。 好ましくは、ステップ(c)は、さらに、第1生成物およびリチウム塩混合物の混合溶液を第1回転速度で粉砕するステップ(c1)と、粉砕を第3の時間行った後、炭素源を添加し、粉砕を継続的に行う、ステップ(c2)と、混合溶液中の平均粒径が第1長さよりも小さく粉砕された後、混合溶液に対して噴霧乾燥を行うステップ(c3)とを含む。 好ましくは、噴霧乾燥の入口温度が210℃であり、出口温度が95℃であり、ターンテーブルの回転速度が300Hz~400Hzである。 第1回転速度は、1分間あたり450~650回転、第3の時間が少なくとも5分間であり、第1長さが1マイクロメートルである。 上記の目的を達成するために、本発明の別の実施形態は、リン酸および鉄粉を提供し、リン酸が鉄粉と反応して第1生成物を生成し、第1生成物が非品質のリン酸鉄であり、化学式がa-FePO4·xH2Oであり、x>0である、ステップ(a)と、リチウム塩混合物を提供し、リチウム塩混合物は、水酸化リチウムと炭酸リチウムとを含有する、ステップ(b)と、第1生成物およびリチウム塩混合物を粉砕混合するステップ(c)と、第1生成物とリチウム塩混合物とを焼結して前駆体を生成し、前駆体の化学式がFe3(PO4)2·8H2O+Li3PO4である、ステップ(d)と、前駆体を焼結してリン酸鉄リチウム正極材料を生成するステップ(e)とを含む、ことを特徴とするリン酸鉄リチウム正極材料の製造方法を提供する。 好ましくは、ステップ(c)は、第1生成物およびリチウム塩混合物の混合溶液を第1回転速度で粉砕するステップ(c1)と、粉砕を第3の時間行った後、炭素源を添加し、粉砕を継続的行う、ステップ(c2)と、混合溶液中の平均粒径が第1長さよりも小さく粉砕された後、混合溶液に対して噴霧乾燥を行うステップ(c3)とを含む。 好ましくは、噴霧乾燥の入口温度が210℃であり、出口温度が95℃であり、ターンテーブルの回転速度が300Hz~400Hzである。 好ましくは、第1回転速度は、1分間あたり450~650回転であり、第3の時間が少なくとも5分間であり、第1長さが1マイクロメートルである。 好ましくは、混合溶液のpH値が7.5~9である。 好ましくは、リチウム塩混合物中の炭酸リチウムのリチウム含有量と水酸化リチウムのリチウム含有量とのモル比が3/7~1である。
Smart Images

Figure 0007644168000004 
Figure 0007644168000005 
Figure 0007644168000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a positive electrode material, and more particularly to a method for producing a lithium iron phosphate positive electrode material for a secondary battery. [Background technology]
[0002] A lithium-ion battery is a secondary battery that can be repeatedly charged and discharged. Lithium ions move between the positive and negative electrodes to achieve charging and discharging. Therefore, lithium-ion batteries must use lithium compounds as electrode materials. The positive electrode materials used in conventional lithium-ion batteries are mainly lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium nickel oxide (LiNiO2), and lithium iron phosphate (LiFePO4). Among them, lithium iron phosphate batteries are widely used in electric vehicles and energy storage devices due to their good safety, large specific capacity, long cycle life, high temperature resistance, and low cost. Among them, for lithium iron phosphate (LiFePO4, also known as LFP) composite material batteries, nano-metal oxide co-crystallized lithium iron phosphate compound (LFP-NCO) batteries have been developed, which contain a single inseparable compound composed of lithium, iron, phosphorus, and metal or metal compound precursors. This can significantly improve the problems of low conductivity and high impurities of traditional lithium iron phosphate materials, and is cheaper than traditional lithium iron phosphate materials, has better market competitiveness, and is widely used as the mainstream material in the current market.
[0003] However, most nano-metal oxide co-crystallized lithium iron phosphate compounds are produced by reacting iron phosphate (FePO4) with lithium hydroxide (LiOH), and the raw material cost of lithium hydroxide is high, and a large amount of iron phosphate raw material is required for production, and it takes a long time to grind the raw material. This increases the unit time and cost of the battery, and the above-mentioned reaction also includes an acid-base neutralization reaction, so the pH value in the production process is sensitive (easily changeable and unstable), and the raw materials are prone to becoming viscous, which may clog the pipeline in the production process. In addition, stable control is difficult due to the heat release and heat absorption caused by the acid-base neutralization reaction, and the production method requires multiple raw material transfers during the production process, which may lead to impurities being mixed in, which may have a significant impact on the quality of the product.
[0004] The present invention has been made in view of the above circumstances, and provides a method for producing a lithium iron phosphate positive electrode material for secondary batteries, which can improve product quality and reduce the costs of raw materials and time, and the difficulty of the manufacturing process, in order to solve the problems faced by the conventional technology. Summary of the Invention [Problem to be solved by the invention]
[0005] The main objective of the present invention is to provide a method for preparing lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material prepared by the precursor Fe3(PO4)2·8H2O+Li3PO4 formation mechanism can solve the problems of high raw material and time costs in the existing battery manufacturing process, and also solve the shortcomings of the acid-base neutralization reaction manufacturing process, such as sensitive pH value, pipeline clogging, difficult temperature control, and pollution caused by repeated transfer of raw materials to tanks.
[0006] Another object of the present invention is to provide a method for preparing a lithium iron phosphate positive electrode material, which is capable of preparing a battery composite material from a precursor formed by reacting an amorphous phosphoric acid body with a lithium salt mixture, greatly shortening the time required for pulverization, and reducing the unit time and cost. It also reduces the sensitivity of the pH value during the preparation process, avoids the viscosity of the raw materials and the clogging of the pipeline, and stably controls the temperature during the preparation process, thereby reducing the difficulty of the preparation process and the operation of the production line.
[0007] Another object of the present invention is to provide a method for producing lithium iron phosphate positive electrode material. The first product produced by reacting phosphoric acid with iron powder is amorphous iron phosphate, which ensures the complete reaction between phosphoric acid and iron powder, effectively reduces the waste of raw materials, and achieves the effect of comprehensively improving the quality of the product. In addition, the lithium salt mixture in a certain ratio range and the first product are ground and mixed, and the pH value of the mixed solution can be stably controlled between 7.5 and 9, reducing the sensitivity of the pH value in the production process, avoiding the viscosity of the raw materials and the blockage of the pipeline, and stably controlling the temperature in the production process, thereby reducing the difficulty of operating the production line in the production process. In addition, since the lithium salt mixture in a certain ratio range contains lithium hydroxide and lithium carbonate, the lithium source in the lithium iron phosphate positive electrode material is not completely provided by lithium hydroxide, but partly provided by lithium carbonate, which not only helps to control the pH value, but also helps to save raw material costs. [Means for solving the problem]
[0008] In order to achieve the above object, an embodiment of the present invention provides a method for preparing a lithium iron phosphate cathode material, the method comprising the steps of: (a) providing phosphoric acid, iron powder, and a carbon source, and reacting the phosphoric acid with the iron powder to produce a first product, the first product being amorphous iron phosphate and having a chemical formula of a-FePO4·xH2O, where x>0; (b) providing a lithium salt mixture, the lithium salt mixture containing lithium hydroxide and lithium carbonate; (c) grinding and mixing the first product, the carbon source, and the lithium salt mixture; (d) sintering the first product and the lithium salt mixture to form a precursor, the precursor having a chemical formula of Fe3(PO4)2·8H2O+Li3PO4; and (e) sintering the precursor and the carbon source to form the lithium iron phosphate cathode material. Preferably, the lithium content of the lithium hydroxide relative to the lithium content of the lithium salt mixture is defined as a first molar fraction, and the first molar fraction is 0.5 to 0.7. Preferably, the lithium content of the lithium carbonate relative to the lithium content of the lithium salt mixture is a second molar fraction, and the second molar fraction is 0.3 to 0.5. Preferably, in step (c), the pH value of the mixture of the first product, the carbon source and the lithium salt is 9 or less. Preferably, in step (c), the mixture of the first product, the carbon source and the lithium salt has a pH value of 7.5-9. Preferably, the lithium iron phosphate positive electrode material is a nano metal oxide co-crystallized lithium iron phosphate compound with a carbon coating (LFP Nano Cocrystalline Olivine, LFP-NCO). Preferably, step (a) further includes the steps of (a1) dissolving a first predetermined amount of the phosphoric acid in deionized water in a first temperature environment to form a first phosphoric acid solution, (a2) reacting the first phosphoric acid solution with iron powder in a second temperature environment, and after reaching a second temperature, lowering the temperature to a third temperature and maintaining it for a first time, and (a3) lowering the temperature to a fourth temperature, adding a second phosphoric acid solution containing a second predetermined amount of phosphoric acid, and reacting the first phosphoric acid solution, the second phosphoric acid solution and the iron powder for a second time to produce a first product. Preferably, the weight ratio of the first predetermined amount to the second predetermined amount is 3:1. Preferably, the first temperature is 35°C to 45°C, the second temperature is 60°C or lower, the third temperature is 50°C or lower, and the fourth temperature is 30°C or lower. Preferably, the first period of time is at least 3 hours and the second period of time is at least 18 hours. Preferably, step (c) further includes the steps of: (c1) grinding the mixed solution of the first product and the lithium salt mixture at a first rotation speed; (c2) adding a carbon source and continuing the grinding after the grinding for a third time; and (c3) spray-drying the mixed solution after the mixed solution is ground to an average particle size smaller than the first length. Preferably, the inlet temperature of the spray drying is 210° C., the outlet temperature is 95° C., and the rotation speed of the turntable is 300 Hz to 400 Hz. The first rotation speed is between 450 and 650 revolutions per minute, the third time period is at least 5 minutes, and the first length is 1 micrometer. In order to achieve the above object, another embodiment of the present invention provides a method for producing a lithium iron phosphate positive electrode material, comprising: step (a) of providing phosphoric acid and iron powder, the phosphoric acid reacting with the iron powder to produce a first product, the first product being non-quality iron phosphate, the chemical formula of which is a-FePO4·xH2O, where x>0; step (b) of providing a lithium salt mixture, the lithium salt mixture containing lithium hydroxide and lithium carbonate; step (c) of grinding and mixing the first product and the lithium salt mixture; step (d) of sintering the first product and the lithium salt mixture to produce a precursor, the chemical formula of which is Fe3(PO4)2·8H2O+Li3PO4; and step (e) of sintering the precursor to produce a lithium iron phosphate positive electrode material. Preferably, step (c) includes the steps of: (c1) grinding the mixed solution of the first product and the lithium salt mixture at a first rotation speed; (c2) adding a carbon source after grinding for a third time and continuing grinding; and (c3) spray-drying the mixed solution after the mixed solution is ground to an average particle size smaller than the first length. Preferably, the inlet temperature of the spray drying is 210° C., the outlet temperature is 95° C., and the rotation speed of the turntable is 300 Hz to 400 Hz. Preferably, the first rotation speed is between 450 and 650 revolutions per minute, the third period of time is at least 5 minutes, and the first length is 1 micrometer. The mixed solution preferably has a pH value of 7.5 to 9. Preferably, the molar ratio of the lithium content of the lithium carbonate to the lithium content of the lithium hydroxide in the lithium salt mixture is 3 / 7-1. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a flow chart of a method for producing a lithium iron phosphate positive electrode material of the present invention. [Diagram 2] FIG. 2 is a detailed flow chart of the method for producing the lithium iron phosphate positive electrode material of the present invention. [Diagram 3] FIG. 2 is another detailed flow chart illustrating the method for producing the lithium iron phosphate cathode material of the present invention. [Figure 4] FIG. 2 is another detailed flow chart illustrating the method for producing the lithium iron phosphate cathode material of the present invention. [Diagram 5] FIG. 2 is an XRD diffraction chart of a precursor in the method for producing a lithium iron phosphate positive electrode material of the present invention. [Figure 6] FIG. 2 is an XRD diffraction chart of the final product obtained by the method for producing the lithium iron phosphate positive electrode material of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Some exemplary embodiments embodying the features and advantages of the present invention will be described in detail in the following. The present invention can be modified in various ways without departing from the scope of the present invention, and the following description and drawings are used to describe the present invention and are not intended to limit the present invention. In addition, in the detailed description of the present invention, the term "a first feature is disposed on or above a second feature" includes an embodiment in which the disposed first feature and the second feature are directly connected to each other, and an embodiment in which the first feature and the second feature are not directly connected to each other through another structure between the first feature and the second feature. Furthermore, in the description of different embodiments in this specification, symbols and / or symbols may be used repeatedly. Such repetition is for the purpose of brevity and clarity, and is not intended to limit the relationship between the various embodiments and / or the exterior structures described. In addition, in the figures, spatial terms such as "inside", "outside", "high", and "low" are described to facilitate the description of the relationship between one component or feature and other (several) components or features. These descriptions are spatially relative terms and are intended to encompass different orientations of the device during use or operation in addition to the orientations shown in the schematic. The device may also be placed in other configurations (e.g., rotated 90 degrees or at other orientations) and may be interpreted according to the context in which it is used. When a component is described as being "connected" or "coupled" to another component, it may be directly connected or coupled to the other component or may be connected or coupled through the other component. Although the numerical ranges and parameters indicating the broad scope of the present specification are approximations, the numerical values set forth in the specific examples are described as being as precise as possible. In addition, the terms "first", "second", "third", etc. are used to describe different configurations described in the claims, and these configurations are not limited to these terms, and in the context of the embodiments, although the corresponding configurations are indicated by different symbols, the first configuration may be indicated as the second configuration and the second configuration may be indicated as the first configuration, without departing from the embodiments of the present invention. In addition, the term "and / or" means one and / or a combination of the associated elements or all of them.Unless expressly defined in the embodiments relating to operation / operation, all numerical ranges, amounts, values, percentages, etc. described herein (e.g., angles, durations, temperatures, operating conditions, ratios and corresponding percentages, etc.) should be understood in all embodiments by the terms "about" or "substantially". In addition, unless otherwise stated in the content, all numerical values in the present invention and claims can be taken as approximations that can be varied as necessary. For example, each parameter may be interpreted in light of at least the number of significant digits described, applying ordinary rounding rules. In addition, numerical ranges herein can be expressed as ranges from one endpoint to the other endpoint or between two endpoints. It should be noted that all ranges described herein include the endpoints unless otherwise defined.
[0011] FIG. 1 is a flow chart of a method for producing a battery composite material in a preferred embodiment of the present invention. As shown in FIG. 1, the method for producing a battery composite material of the present invention includes the following steps. As shown in step S100, phosphoric acid, iron powder, and a carbon source (sugar, organic compound, polymer, or polymer material) are provided (prepared, prepared). Note that the chemical formula of phosphoric acid is H3PO4, and the chemical formula of iron powder is Fe. In an embodiment, the sugar may be, for example, fructose, sucrose, lactose, galactose, etc., but is not limited thereto. The polymer material may be, for example, polyvinylpyrrolidone (PVP, chemical formula (C6H9NO) n ), but the present invention is not limited thereto. Phosphoric acid reacts with iron powder to produce a first product. In this embodiment, the first product is amorphous iron phosphate, which has the chemical formula a-FePO4·xH2O, where x is greater than 0.
[0012] Also, as in step S200, a lithium salt mixture is provided, and the lithium salt mixture is lithium carbonate (chemical formula Li2CO3) and lithium hydroxide (chemical formula LiOH). Note that the lithium carbonate and lithium hydroxide in the lithium salt mixture have a certain ratio range. In this embodiment, the molar fraction of the lithium content of the lithium hydroxide relative to the lithium content of the lithium salt mixture is a first molar fraction, and the first molar fraction is preferably 0.5 to 0.7. Also, the molar fraction of the lithium content of the lithium carbonate relative to the lithium content of the lithium salt mixture is a second molar fraction, and the second molar fraction is preferably 0.3 to 0.5. In other words, the lithium in the lithium iron phosphate positive electrode material is not completely provided by lithium hydroxide, and the molar ratio of the lithium content of the lithium carbonate to the lithium content of the lithium hydroxide in the lithium salt mixture is 3 / 7 to 1. By replacing some of the lithium hydroxide with lithium carbonate, the pH sensitivity of the downstream manufacturing process can be reduced, raw material viscosity and pipeline blockages can be avoided, and the temperature of the manufacturing process can be stably controlled, which is also advantageous in reducing raw material costs.
[0013] As shown in step S300, the first product and the lithium salt mixture are pulverized, and a carbon source is added during the pulverization process. As shown in step S400, the pulverized and mixed first product and the lithium salt mixture are sintered to generate a precursor, the chemical formula of which is Fe3(PO4)2·8H2O+Li3PO4.
[0014] Finally, as shown in step S500, the precursor and the carbon source are sintered to react with each other to produce a lithium iron phosphate cathode material LiFePO4. In another embodiment, metal oxides such as V2O5, MgO, etc. may be added in step S300. This can provide a LiFePO4 material containing metal oxides. The LiFePO4 material containing metal oxides can be called "nano metal oxide co-crystallized lithium iron phosphate compound (LFP-NCO)". However, the present invention is not limited thereto.
[0015] As described above, the method for producing the lithium iron phosphate positive electrode material of the present invention can ensure the complete reaction of phosphoric acid with iron powder by (through the production process of) the first product produced by the reaction of phosphoric acid with iron powder, effectively reducing the waste of raw materials and improving the quality of the product. In addition, the lithium salt mixture contains lithium hydroxide and lithium carbonate at a certain ratio, and is mixed with the first product through grinding, thereby reducing the sensitivity of the pH value during the production process, avoiding the viscosity of the raw materials and the clogging of the pipeline, and stably controlling the temperature during the production process, which is also advantageous in reducing the cost of raw materials.
[0016] Please refer to FIG. 2 together with FIG. 1. FIG. 2 is a detailed flow chart of the method for producing the lithium iron phosphate positive electrode material of the present invention. As shown in FIG. 1 and FIG. 2, step S100 of the method for producing the lithium iron phosphate positive electrode material of the present invention further includes the following detailed steps. As shown in step S101, in a first temperature environment (for example, an environment of 35°C to 45°C), a first predetermined amount of phosphoric acid is dissolved in deionized water to form a first phosphoric acid solution. Here, an environment preheated to 42°C is preferable, but the present invention is not limited thereto. Next, as shown in step S102, in a second temperature environment, the first phosphoric acid solution is reacted with iron powder, and when the second temperature is reached, the temperature is lowered to a third temperature and the state is maintained for a first time. According to the technical idea of the present invention, the iron powder can be reacted with other compounds that can release phosphate ions in the solution after mixing, but the present invention is not limited thereto. In addition, the second temperature is 60°C or less, but preferably 60°C. The third temperature is 50°C or less, but preferably 50°C. The first time is at least 3 hours, and preferably 3 hours.
[0017] In other words, the preferred embodiment of step S102 is to react the first phosphoric acid solution with the iron powder in an environment of 60°C, and then lower the temperature to 50°C after reaching 60°C, and maintain for 3 hours, but the present invention is not limited thereto. Then, as shown in step S103, lower the temperature to a fourth temperature, add a second phosphoric acid solution containing a second predetermined amount of phosphoric acid, and react the first phosphoric acid solution, the second phosphoric acid solution and the iron powder continuously for a second time to produce a first product.
[0018] In this embodiment, the first product is an amorphous body of iron phosphate, the chemical formula of which is a-FePO4·xH2O (x>0), and the fourth temperature is less than or equal to 30°C, preferably 30°C. The second time is at least 18 hours, preferably 18 hours. The weight ratio of the first predetermined amount to the second predetermined amount is 3:1, that is, the first predetermined amount is 75%, and the second predetermined amount is 25%. The phosphoric acid solution and the iron powder can be fully reacted through the secondary reaction (second reaction) of phosphoric acid, deionized water and iron powder, which can effectively reduce the waste of raw materials and comprehensively improve the quality of the product.
[0019] After the above-mentioned reaction is completed for 18 hours, step S300 of the method for producing a lithium iron phosphate positive electrode material of the present invention is carried out. The detailed steps are described below. As shown in FIG. 3, a detailed flow chart of the method for producing a lithium iron phosphate positive electrode material of the present invention is shown. First, as shown in step S301 of FIG. 3, the first product is pulverized at a first rotation speed. The first rotation speed is 450 to 650 rotations per minute (450-650 rpm), and preferably 550 rotations per minute (550 rpm).
[0020] Further, as shown in step S302, during the grinding operation, add a carbon source and a lithium salt mixture in a certain ratio range, and after a third time, for example, at least 5 minutes, add a carbon source and a lithium salt mixture (the carbon source is, for example, a polymer material PVP) to generate a precursor solution, and at the same time, continue the grinding operation, and measure the average particle diameter (i.e., the average particle diameter D 50After the powder is ground to a first length (diameter, for example, but not limited to, less than one micrometer (1 μm)), the precursor solution is spray-dried and heat-treated to obtain a dried precursor, the chemical formula of which is Fe3(PO4)2·8H2O+Li3PO4.
[0021] Spray drying is achieved by a turntable type spray dryer, with an inlet temperature of 210° C., an outlet temperature of 95° C., and a turntable rotation speed of 300-400 Hz, although the present invention is not limited thereto.
[0022] Up to this point, the process of forming the precursor of the method for producing the lithium iron phosphate positive electrode material of the present invention has been described, and the details of the subsequent step S500 will be described below. FIG. 4 is a detailed flow chart of the method for producing the lithium iron phosphate positive electrode material of the present invention. As shown in FIG. 4, in step S501, the first product, the lithium salt mixture, and the carbon source are pulverized and mixed to form a precursor solution. Next, as shown in step S502, a dispersant is added and spray granulation is performed. Next, as shown in step S503, high-temperature sintering is performed. Finally, as shown in step S504, the lithium iron phosphate positive electrode material of the present invention (whose chemical formula is LiFePO4) is produced.
[0023] Hereinafter, the method for producing the lithium iron phosphate positive electrode material of the present invention will be described using exemplary embodiments.
[0024] Example 1 Provide 518.6g phosphoric acid (purity 85% or more), deionized water and 253g iron powder (purity 99% or more) to generate the first product in the primary reaction (first reaction). Add a lithium salt mixture, and the lithium salt mixture contains 95.33g lithium hydroxide (concentration 50wt.%) and 83.78g lithium carbonate. That is, the molar ratio of the lithium content of the lithium carbonate and the lithium content of the lithium hydroxide in the lithium salt mixture is 1:1, and each is used as a 50% lithium source. After 20 hours of stirring and co-reaction, control the pH value to 7.9, add a dispersant and grind using a horizontal sand mill (rotation speed 450-650 rpm), and during the grinding process, add a carbon source (sugars, organic compounds, polymers or polymeric materials, among which the polymeric materials are, for example, PVP) to obtain a precursor solution containing Fe3(PO4)2·8H2O+Li3PO4. Then, spray-dry the precursor solution. Next, the finished product after spray drying was placed in a long-diameter ceramic crucible and sintered to obtain the precursor. The X-ray diffraction (XRD) analysis results are shown in Figure 5, and compared with the standard diffraction pattern (JCPDS Card), it was found that the structure was Fe3(PO4)2·8H2O+Li3PO4.
[0025] The spray-dried precursor is then kept in an inert gas at 550°C for 4 hours and at 700°C for 4 hours to obtain the lithium iron phosphate cathode material of the present invention. The X-ray diffraction result of the compound obtained after sintering is shown in Figure 6, and it was confirmed that the structure is lithium iron phosphate LiFePO4. In addition, the powder of the lithium iron phosphate cathode material obtained has an average particle size of 14.00 μm and a specific surface area of 19.88 m 2 / g and the electroanalysis results are shown in Table 1. JPEG0007644168000001.jpg34164
[0026] Example 2 Provide 518.6g phosphoric acid (purity 85% or more), deionized water and 253g iron powder (purity 99% or more) to produce the first product in the primary reaction (first reaction). The lithium salt mixture added in Example 2 is different from Example 1, containing 114.4g lithium hydroxide (concentration 50wt.%) and 67.02g lithium carbonate. That is, the molar ratio of the lithium content of lithium carbonate and the lithium content of lithium hydroxide in the lithium salt mixture is 2:3, and lithium carbonate and lithium hydroxide are used as lithium sources of 40% and 60%, respectively. After 20 hours of stirring and co-reaction, control the pH value to 8.2. Add a dispersant and grind for hours using a horizontal sand mill (rotation speed 450-650 rpm). During the grinding process, add a carbon source to obtain a precursor solution of Fe3(PO4)2·8H2O+Li3PO4. Next, the spray-dried precursor is held in an inert gas at 550°C for 4 hours and then at 700°C for 4 hours, after which the lithium iron phosphate positive electrode material LiFePO4 of the present invention can be obtained. The powder of the obtained lithium iron phosphate positive electrode material has an average particle size of 17.96 μm and a specific surface area of 20.63 m 2 / g and the electroanalytical results are shown in Table 2. JPEG0007644168000002.jpg34164
[0027] Example 3 Provide 518.6g phosphoric acid (purity 85% or more), deionized water and 253g iron powder (purity 99% or more) to generate the first product in the primary reaction (first reaction). The lithium salt mixture added in Example 3 is different from that in Example 1, and contains 133.47g lithium hydroxide (concentration 50wt.%) and 50.27g lithium carbonate. That is, the molar ratio of the lithium content of lithium carbonate to the lithium content of lithium hydroxide in the lithium salt mixture is 3:7, and lithium carbonate and lithium hydroxide are used as 30% and 70% lithium sources, respectively. After 20 hours of stirring and co-reaction, control the pH value to 8.4. Add a dispersant and grind with a horizontal sand mill (rotation speed 450-650 rpm) for 1 hour. During the grinding process, add a carbon source to obtain a precursor solution of Fe3(PO4)2·8H2O+Li3PO4. The spray-dried precursor is kept in an inert gas at 550° C. for 4 hours and then at 700° C. for 4 hours, after which the lithium iron phosphate positive electrode material LiFePO4 of the present invention can be obtained. The powder of the obtained lithium iron phosphate positive electrode material has an average particle size of 13.00 μm and a specific surface area of 18.87 m 2 / g and the electroanalytical results are shown in Table 3. JPEG0007644168000003.jpg34164
[0028] From the results of electrical analysis of the lithium iron phosphate positive electrode material obtained in Examples 1 to 3, the present invention has found that the specific surface area of the lithium iron phosphate positive electrode material produced by the precursor Fe3(PO4)2·8H2O+Li3PO4 formation mechanism is 18m 2 / g~21m 2 / g, and the 0.1C charge / discharge capacity exceeds 150mAh / g, and the material has excellent physical properties and electrical properties. The method for producing the lithium iron phosphate positive electrode material of the present invention can produce a lithium iron phosphate positive electrode material with the required product specifications by adjusting many of the process parameters described above. However, the present invention is not limited thereto.
[0029] As described above, the present invention provides a method for preparing lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material prepared by the mechanism of precursor Fe3(PO4)2·8H2O+Li3PO4 can solve the problems of high cost of raw materials and time in the existing battery manufacturing process, and can also solve the disadvantages of the sensitive pH value in the manufacturing process due to acid-base neutralization reaction, clogging of pipelines, difficulty in temperature control, and pollution caused by repeatedly transferring raw materials to tanks. Among them, the preparation of battery composite materials using a precursor formed by reacting an amorphous phosphoric acid body with a lithium salt mixture can greatly shorten the time required for grinding, and reduce the unit time and cost. In addition, the sensitivity of the pH value in the manufacturing process can be reduced, the viscosity of raw materials and clogging of pipelines can be avoided, and the temperature in the manufacturing process can be stably controlled, thereby reducing the difficulty of the manufacturing process and the operation of the production line. In addition, the first product generated by the reaction of phosphoric acid with iron powder is amorphous iron phosphate, which ensures the complete reaction of phosphoric acid with iron powder, effectively reduces the waste of raw materials, and achieves the effect of comprehensively improving the quality of products. In addition, the lithium salt mixture in a certain ratio range and the first product are pulverized and mixed, and the pH value of the mixed solution can be stably controlled between 7.5 and 9, which reduces the sensitivity of the pH value in the manufacturing process, avoids the viscosity of the raw materials and the blockage of the pipeline, and stably controls the temperature in the manufacturing process, thereby reducing the difficulty of operating the production line in the manufacturing process. In addition, since the lithium salt mixture in a certain ratio range contains lithium hydroxide and lithium carbonate, the lithium source in the lithium iron phosphate positive electrode material is not entirely provided by lithium hydroxide, but is partially provided by lithium carbonate, which not only helps to control the pH value but also helps to save raw material costs.
[0030] The present invention can be modified or changed in various ways by those skilled in the art, but all such modifications and changes are within the scope of the claims of the present invention without departing from the technical spirit of the present invention.
[0031] S100, S101, S102, S103, S200, S300, S301, S302, S303, S400, S500, S501, S502, S503, S504: Step
Claims
1. providing phosphoric acid, iron powder, and a carbon source, said phosphoric acid reacting with said iron powder to produce a first product, said first product being amorphous iron phosphate having a chemical formula of a-FePO 4 ・xH 2 O, and x>0; and (b) providing a lithium salt mixture, the lithium salt mixture containing lithium hydroxide and lithium carbonate; (c) grinding and mixing the first product, the carbon source and the lithium salt mixture; sintering the first product with the lithium salt mixture to form a precursor having a chemical formula of Fe 3 (P.O. 4 ) 2 ・8H 2 O + Li 3 P.O. 4 and step (d), and (e) sintering the precursor and the carbon source to form a lithium iron phosphate cathode material.
2. 2. The method of claim 1, wherein a lithium content of the lithium hydroxide relative to a lithium content of the lithium salt mixture is a first mole fraction, and the first mole fraction is 0.5 to 0.
7.
3. 2. The method of claim 1, wherein the lithium content of the lithium carbonate relative to the lithium content of the lithium salt mixture is a second molar fraction, and the second molar fraction is 0.3 to 0.
5.
4. 2. The method of claim 1, wherein in step (c), the pH value of the mixture of the first product, the carbon source and the lithium salt is 9 or less.
5. 2. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, wherein in step (c), the pH value of the mixture of the first product, the carbon source and the lithium salt is 7.5-9.
6. 2. The method for producing the lithium iron phosphate positive electrode material according to claim 1, wherein the lithium iron phosphate positive electrode material is a nano-metal oxide co-crystallized lithium iron phosphate compound with a carbon coating.
7. The step (a) further comprises: (a1) dissolving a first amount of the phosphoric acid in deionized water in a first temperature environment to form a first phosphoric acid solution; (a2) reacting the first phosphoric acid solution with the iron powder in a second temperature environment, and after reaching the second temperature, lowering the temperature to a third temperature and maintaining it for a first time; and (a3) decreasing the temperature to a fourth temperature, adding a second phosphoric acid solution containing a second predetermined amount of the phosphoric acid, and reacting the first phosphoric acid solution, the second phosphoric acid solution, and the iron powder for a second time to produce the first product.
8. 8. The method of claim 7, wherein the weight ratio of the first predetermined amount to the second predetermined amount is 3:
1.
9. 8. The method for producing a lithium iron phosphate positive electrode material according to claim 7, wherein the first temperature is 35° C. to 45° C., the second temperature is 60° C. or less, the third temperature is 50° C. or less, and the fourth temperature is 30° C. or less.
10. 8. The method of claim 7, wherein the first period of time is at least 3 hours and the second period of time is at least 18 hours.
11. The step (c) further comprises: (c1) grinding the mixed solution of the first product and the lithium salt mixture at a first rotation speed; (c2) adding the carbon source after the grinding for a third time and continuing the grinding; and 2. The method for producing a lithium iron phosphate positive electrode material according to claim 1, further comprising: (c3) spray-drying the mixed solution after the mixed solution is pulverized so that the average particle size in the mixed solution is smaller than the first length.
12. The method for producing a lithium iron phosphate positive electrode material according to claim 11, characterized in that the inlet temperature of the spray drying is 210°C, the outlet temperature is 95°C, and the rotation speed of the turntable is 300Hz to 400Hz.
13. 12. The method of claim 11, wherein the first rotation speed is between 450 and 650 revolutions per minute, the third time period is at least 5 minutes, and the first length is 1 micrometer.
14. providing phosphoric acid and iron powder, said phosphoric acid reacting with said iron powder to produce a first product, said first product being amorphous iron phosphate having a chemical formula of a-FePO 4 ・xH 2 O, and x>0; and (b) providing a lithium salt mixture, the lithium salt mixture containing lithium hydroxide and lithium carbonate; (c) grinding and mixing the first product and the lithium salt mixture; sintering the first product with the lithium salt mixture to form a precursor, the precursor having a chemical formula of Fe 3 (P.O. 4 ) 2 ・8H 2 O + Li 3 P.O. 4 and step (d), and (e) sintering the precursor to form a lithium iron phosphate cathode material.
15. The step (c) (c1) grinding the mixed solution of the first product and the lithium salt mixture at a first rotation speed; After the grinding for a third time, a carbon source is added and the grinding is continued, step (c2); 15. The method for producing a lithium iron phosphate positive electrode material according to claim 14, further comprising: (c3) spray-drying the mixed solution after the mixed solution is pulverized so that the average particle size in the mixed solution is smaller than the first length.
16. 16. The method for producing a lithium iron phosphate positive electrode material according to claim 15, wherein the inlet temperature of the spray drying is 210° C., the outlet temperature is 95° C., and the rotation speed of the turntable is 300 Hz to 400 Hz.
17. 16. The method of claim 15, wherein the first rotation speed is between 450 and 650 revolutions per minute, the third time period is at least 5 minutes, and the first length is 1 micrometer.
18. The method for producing a lithium iron phosphate positive electrode material according to claim 15, wherein the pH value of the mixed solution is 7.5 to 9.
19. 15. The method for producing a lithium iron phosphate positive electrode material according to claim 14, wherein the molar ratio of the lithium content of the lithium carbonate to the lithium content of the lithium hydroxide in the lithium salt mixture is 3 / 7 to 1.
Citation Information
Patent Citations
Method for manufacturing composite materials for batteries and their precursors
JP2014524123A
A process for preparing lithium iron phosphorus based composite oxide carbon complex doped nikel oxide
KR1020170136779A